Seoul [videorecording] a metropolis embraces tradition - Kin Misook; Lee Hongki; Digital media ([S.l.] Arirang TV)
Explores Korea's principal city, its traditional and modern ways of life.
This program is sponsored by Korea Foundation.
VHS.
Director of photography, Lee Kilho; Editor, Lee Joonkyu, song Sangyup; Narrator, Dianne Sadak.
Keywords: Seoul (Korea) -- Description and travel; Korea -- History; Seoul (Korea) -- Social life and customs